Plasmid-mediated quinolone resistance determinants in fluoroquinolone-nonsusceptible Escherichia coli isolated from patients with urinary tract infections in a university hospital, 2009–2010 and 2020. (September 2022) - Kuo, Pei-Yun; Lo, Yu-Ting; Chiou, Yu-Jing; Chen, Chao-An; Hidrosollo, Jazon Harl; Thuy, Tran Thi Dieu; Zhang, Yen-Zhen; Wang, Ming-Cheng; Lin, Tzu-Ping; Lin, Wei-Hung; Kao, Cheng-Yen
Highlights: The prevalence of FQNSEC in UTI E. coli was stable in 2009-2010 and 2020. Phylogenetic group B2 was dominant in FQNSEC isolates, followed by group F, group B1, and group D. A high prevalence rate of MDR- and XDE- E. coli was observed in FQNSEC. FQNSEC isolates had less virulence factor genes compared to FQ susceptible isolates. qnr -carrying plasmids in FQNSEC were highly transferable and lead to resistance to other classes of antibiotics in the transconjugants. Abstract: Objectives: This study aimed to characterize the plasmid-mediated quinolone resistance (PMQR) in fluoroquinolone nonsusceptible E. coli (FQNSEC) isolated from patients with urinary tract infections (UTIs) in 2019–2010 and 2020. Methods: A total of 844 E. coli isolates were collected from UTI patients at National Cheng Kung University Hospital. The antimicrobial susceptibility of E. coli isolates to 21 antibiotics was determined by disk diffusion tests. The distribution of phylogenetic groups, virulence factor, and PMQR genes was determined by PCR. Conjugation assays were performed to investigate the transferability of qnr genes from FQNSEC isolates to E. coli C600. Results: We found 211 (41.9%) and 152 (44.7%) E. coli isolates were FQNSEC in 2009–2010 and 2020, respectively. Phylogenetic group B2 was dominant in FQNSEC isolates (52.34%), followed by group F (10.47%), group B1 (9.64%), and group D (9.64%). FQNSEC isolates were more resistant to 17 of 19 tested antimicrobial agents, compared to the fluoroquinolone susceptible E. coli . PMQR screening results showed 34, 22, and 10 FQNSEC isolates containing aac(6′)-Ib-cr, qnr genes, and efflux pump genes ( qepA or oqxAB ), respectively. PMQR E. coli isolates were more nonsusceptible to gentamicin, amoxicillin, ampicillin/sulbactam, imipenem, cefazolin, cefuroxime, cefmetazole, ceftriaxone, ceftazidime, and cefepime compared to non-PMQR FQNSEC. Moreover, 16 of 22 qnr -carrying plasmids were transferrable to the recipient C600. Conclusion: Here, we reported the high prevalence of MDR- and XDR- E. coli in FQNSEC isolates. Moreover, qnr -carrying plasmids were highly transferable and led to the resistance to other classes of antibiotics in the transconjugants.